Health Hygiene and Nutrition Practices Through the Psycho-Educational Group Approach - Itratulhuda Abdullah Alim; Mohd Izwan Mahmud (Education and Social Sciences Review, 2020)
This study aims to provide exposure to hygiene management and healthy eating practices among primary school students. This study is a case study using a psycho-educational approach with 4 cohort counseling sessions. The cohort sample consisted of 13 primary school students aged 7 to 9. They are 1st grade boys and girls in a transit center (tahfiz) in Bandar Baru Bangi. The findings show that group members have a sense of responsibility for personal hygiene and environment as well as knowledge of healthy and clean eating practices for daily living. The findings of the study also found that the psycho-educational approach to group counseling is very effective in helping students improve their awareness of hygiene and healthy eating. The application of good hygiene elements and nutrition practices should be taken into account in order for the child's physical growth to thrive and to achieve academic success while minimizing health problems. The importance of hygiene and healthy eating through psycho education has implications for students, teachers in tahfiz centers and parents. They play a role in educating children on personal hygiene, environment and healthy eating habits as a very effective measure to prevent the risk of attacking diseases that impede children's development.